Morpho-biochemical diversity in tree tomato (Solanum betaceum Cav.) genotypes grown under different altitudinal locations of north eastern Himalayas of India - Sita Kumari Prasad; Ankita Debnath
Seventeen tree tomato (Solanum betaceum Cav.) genotypes were evaluated for their morpho-biochemical diversity in Randomized Block Design under three replications at Sikkim University, Gangtok in 2017-18. The genotypes were grouped into five clusters and cluster I possessed highest number of genotypes (6). Highest inter-cluster distance (372237) was recorded between clusters II & V. Intra-cluster was maximum in cluster III (28651.72) showing diversity within the cluster. The genotype STT-110 produced maximum value for average fruit weight (81 g) and other fruit yield contributing characters. Whereas, STT-40 produced maximum values for iron (1.86 mg/100 g), copper (0.47 mg/100 g) and manganese (1.38 mg/100 g). Genetic parameters (PCV, GCV) along with heritability and genetic advance were highest for anthocyanin (77.26%, 77.19%, 99% and 158.85%), flavonoid (56.91%, 56.90%, 100% and 117.22%), total phenol (52.76%, 52.72%, 99%, and 108.54%), manganese (50.87%, 49.26%, 93%, and 98.28%) and ascorbic acid (41.73%, 41.71%, 99% and 85.89%). Correlation coefficient analysis showed that polar and equatorial diameter of fruit was significantly correlated with average fruit weight. Genotypic correlation coefficients were higher than phenotypic correlation coefficients, which indicate the inherent association among the characters. This study highlights the potential utilization of STT-110 genotype for further selection in future breeding programme for enhancing yield.